2022
DOI: 10.3389/fpls.2022.926197
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids metabolism and physiological response to ultraviolet treatments in Tetrastigma hemsleyanum Diels et Gilg

Abstract: Tetrastigma hemsleyanum Diels et Gilg is a folk herb in Zhejiang Province with anti-inflammatory, antineoplastic, and anti-oxidation effects. Given its pharmacological activity, T. hemsleyanum is known as New "Zhebawei" and included in the medical insurance system of Zhejiang and other provinces. Flavonoids are the most important components of T. hemsleyanum, and their contents are mainly regulated by ultraviolet (UV) radiation. In this study, the total flavonoid contents, flavonoid monomer contents, and flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For example, flavonoids can help plants resist adverse environmental conditions. Some studies have shown that flavonoids can enhance the antioxidant capacity of plants and reduce the damage caused by harmful substances such as ultraviolet rays and free radicals 46 . In addition, it has been reported that flavonoids can also improve the disease resistance of plants 47 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, flavonoids can help plants resist adverse environmental conditions. Some studies have shown that flavonoids can enhance the antioxidant capacity of plants and reduce the damage caused by harmful substances such as ultraviolet rays and free radicals 46 . In addition, it has been reported that flavonoids can also improve the disease resistance of plants 47 .…”
Section: Discussionmentioning
confidence: 99%
“…When plants receive abiotic stress factors, such as UV radiation, they will produce some secondary metabolites in response to this stress [21][22][23]. Flavonoids are important secondary metabolites in plants that respond to external abiotic stress [24,25]. When plants receive high doses of UV-B radiation, the plant leaves show severe wilting and curling.…”
Section: In Vitro Characterization Of Recombinant Elomt1mentioning
confidence: 99%
“…Once absorbed, they enter the portal circulation, which brings structural changes in the molecules that alter their properties. Therefore, it is essential to consider how intestinal digestion and microbiota affect their uptake, metabolization, and bioavailability (199). Some studies also show that flavonoids enhance the production of glucagon-like-peptide (GLP-1) production, which positively affects gut bacteria (200).…”
Section: Future Perspectivesmentioning
confidence: 99%